"Fault‐line of an Earthquake": A Qualitative Examination of Barriers and Facilitators to Colorectal Cancer Screening in Rural, Eastern North Carolina. Issue 1 (1st August 2012) - Jilcott Pitts, Stephanie B.; Lea, C. Suzanne; May, Carrie L.; Stowe, Chelsea; Hamill, Dana J.; Walker, Kelcy T.; Fitzgerald, Timothy L.
Abstract Purpose: Colorectal cancer (CRC) is a leading cause of cancer mortality and disparately affects rural, low‐income and minority individuals. Thus, to inform effective interventions and policies to increase screening rates and thus ameliorate CRC disparities, this study's purpose was to examine barriers and facilitators to CRC screening among low‐income, rural eastern North Carolina residents. Methods: We conducted 4 focus group discussions in October and November 2011, among a convenience sample of eastern North Carolina residents (n = 45). The focus group discussion guide included open‐ended questions about barriers and facilitators to CRC screening. Discussions were audio recorded and then transcribed verbatim. A codebook listing codes and operational definitions was developed by 2 research team members, who then iteratively and independently double‐coded all transcripts. Nvivo (version 9, QSR International Pty Ltd, Doncaster, Victoria, Australia) was used to manage data. Themes were extracted based upon depth and frequency of mention. Findings: Major barriers to CRC screening included the high cost of tests and follow‐up care, fear of the test itself (colonoscopy), fear of cancer diagnosis, and fear of burdening family members. Violation (among men) and embarrassment (among women) were also barriers. Facilitators included doctor's recommendation, symptoms, support from family and friends, and the desire to live a long and healthy life. Intervention ideas included free tests with information and resources for follow‐up care as needed. Conclusion: Understanding barriers and facilitators to CRC screening can assist clinicians and public health practitioners in designing effective interventions to reduce CRC disparities.